2012
DOI: 10.1002/etc.1823
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced changes in trace element bioaccumulation and proteomics perspective in four marine bivalves

Abstract: Bivalves are employed widely as biomonitors of metal pollution and proteomics has increasingly been applied to solve ecotoxicological issues. This study aimed to investigate the effects of Cd exposure on the bioaccumulation of other trace elements and reveal the molecular mechanisms using proteomics technologies. The results showed that Cd exposure resulted in remarkable changes in body concentrations of Zn, Cu, Ag, Co, Ni, Pb, and Se in four marine bivalves (scallop Chlamys nobilis, clam Ruditapes philippinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Actually, many pathology studies have shown the feasibility of disease diagnosis and prediction based solely on the molecular expression patterns, independent of biological knowledge of the molecules [37,38]. Recently, the concept of protein expression pattern/signature (PES) evolved from these human clinical proteomics has been increasingly applied in environmentally relevant organisms [15][16][17]32]. PES is defined as a set of proteins as biomarkers of specific environmental stressors.…”
Section: Expression Pattern Of Proteome In the Oystersmentioning
confidence: 99%
See 3 more Smart Citations
“…Actually, many pathology studies have shown the feasibility of disease diagnosis and prediction based solely on the molecular expression patterns, independent of biological knowledge of the molecules [37,38]. Recently, the concept of protein expression pattern/signature (PES) evolved from these human clinical proteomics has been increasingly applied in environmentally relevant organisms [15][16][17]32]. PES is defined as a set of proteins as biomarkers of specific environmental stressors.…”
Section: Expression Pattern Of Proteome In the Oystersmentioning
confidence: 99%
“…The gill proteome was visualized by a silver staining method compatible with MS analysis, and the detailed procedures are described in our previous study [32]. The silver staining allows for detection of <1 ng protein per spot, and the method has proven effective in quantification and mass spectrometric sequencing of proteins [21,32,33].…”
Section: Proteomic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The third group (Cd+ La -exposed group) were exposed to Cd 2+ (20 μg/L) throughout the experiment and challenged with L . anguillarum (5×10 6 CFU/mL) after 48 h. The concentration of Cd used in the experiment (20 μg/L) is similar to that at several points along the Bohai coast and has been used by many researchers to study the adverse effects of cadmium on the mollusks (Zhang, 2001;Wu and Wang, 2011;Liu et al, 2012). When appropriate, Cd 2+ and L .…”
Section: Animals and Treatmentsmentioning
confidence: 99%